Employee's subjective-well-being and job discretion: Designing gendered happy jobs - Maria Bastida; Isabel Neira; Maricruz Lacalle-Calderon (European Research on Management and Business Economics (ERMBE), 2022)
This paper analyses the influence of job discretion on employees' subjective well-being (SWB) from a gender-based approach. Specifically, it explores whether the level of discretion given to employees in performing their jobs influences their SWB and whether this impact differs between women and men. Data from 20 European countries from Round 8 of the European Social Survey (ESS) are used to undertake an ordered probit analysis. Job discretion is approached through autonomy at work, supervision of other employees and influence on organisational policy decisions. Additionally, the individual's educational level is controlled to further explore gendered differences of job characteristics on SWB. The results show that job discretion does indeed affect SWB, and this effect is different for women and men. Moreover, the effect of job discretion on SWB is not homogeneous across different education levels.
Keywords: C55; I31; Z13; 650; Educational level; Gender; Job discretion; Probit analysis; Subjective well-being